2020
DOI: 10.52922/sb04718
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of domestic violence among women during the COVID-19 pandemic

Abstract: This paper presents the findings from an online survey of 15,000 Australian women about their experience of domestic violence during the initial stages of the COVID-19 pandemic. In the three months prior to the survey, conducted in May 2020, 4.6 percent of women who responded to the survey experienced physical or sexual violence from a current or former cohabiting partner. Almost six percent (5.8%) of women experienced coercive control and 11.6 percent reported experiencing at least one form of emotionally abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
2
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(130 citation statements)
references
References 0 publications
6
118
2
4
Order By: Relevance
“…Increase in the frequency and severity of domestic violence Not surprisingly, 13.1% (n = 41) of service providers indicated that victims/survivors who were locked down and isolated with violent partners experienced an increase in domestic violence, including an increase in coercive and controlling behaviours. This aligns with other research undertaken during the pandemic that has found more than half the women who had experienced domestic violence prior to COVID-19 indicated that the intensity of it had become more frequent and/or severe during the pandemic (Boxall, Morgan and Brown 2020;Pfitzner, Fitz-Gibbon and True 2020). Supporting findings from these studies, our survey similarly revealed that being stuck at home with the perpetrator led to worsening violence in some instances.…”
Section: Needs In Australiasupporting
confidence: 89%
See 3 more Smart Citations
“…Increase in the frequency and severity of domestic violence Not surprisingly, 13.1% (n = 41) of service providers indicated that victims/survivors who were locked down and isolated with violent partners experienced an increase in domestic violence, including an increase in coercive and controlling behaviours. This aligns with other research undertaken during the pandemic that has found more than half the women who had experienced domestic violence prior to COVID-19 indicated that the intensity of it had become more frequent and/or severe during the pandemic (Boxall, Morgan and Brown 2020;Pfitzner, Fitz-Gibbon and True 2020). Supporting findings from these studies, our survey similarly revealed that being stuck at home with the perpetrator led to worsening violence in some instances.…”
Section: Needs In Australiasupporting
confidence: 89%
“…This comment also signals the other main reason why accessing formal supports was more difficult for victims/survivors of domestic violence during COVID-19: increased control by proximity to and surveillance from the perpetrator (see Figure 5). This was noted by almost one-third of respondents (29.8%, n = 39) (see also Boxall, Morgan and Brown 2020;Pfitzner, Fitz-Gibbon and True 2020). As these responses capture:…”
Section: Reduction In Supports Available For Victims/survivorsmentioning
confidence: 89%
See 2 more Smart Citations
“…A study by Ravindran and Shah ( 2020 ) conducted in India similarly found an increase in domestic violence and cybercrime complaints after shelter-in-place orders were initiated, with increases most concentrated in districts with the strictest lockdown orders. In Australia, Boxall and colleagues ( 2020 ) sent an online survey to 15,000 women about their experiences of domestic violence during the initial three months of the COVID-19 pandemic. Results suggested that the pandemic coincided with the onset or escalation of violence and abuse among many Australian women.…”
Section: Literature Reviewmentioning
confidence: 99%